Effect of Long Exposure to ELF Electromagnetic Field Radiation Intensity 500 µT on Morphology and Spermatozoa Population of Balb/C Mice - Moza Oriana Rahmadinanti; Firdha Kusuma Ayu Anggraeni; Sudarti Sudarti (BULETIN FISIKA, 2025)
Along with the era of development, the use of Extremely Low Frequency (ELF) electromagnetic field radiation, which has a very low frequency of 0-300 Hz, is increasingly widespread. Its impact on spermatozoa remains contradictory and requires further study. Therefore, this study aims to examine the effect of long-term exposure to ELF electromagnetic field radiation with an intensity of 500 µT on the population and morphology of Balb/C mice spermatozoa. This study uses a true experimental design with a pretest-posttest control group design. There are several tools used in this research. One of them is the ELF generator as an ELF electromagnetic field generating device. The method used in sampling mice spermatozoa is eosin staining and haemocytometer. Exposure to ELF electromagnetic fields with an intensity of 500 µT was carried out intermittently, namely 15 and 60 minutes, twice a day, and given for 5 days. The results showed that exposure to the ELF electromagnetic field did not have a significant effect on the population of Balb/C mice spermatozoa, but had a significant effect on spermatozoa morphology. The effect of magnetic fields and electric fields on the population and morphology of spermatozoa differs; namely, the electric field has a more dominant effect on the population and morphology of abnormal spermatozoa, while the magnetic field has a more dominant effect on the morphology of normal spermatozoa.